2013
DOI: 10.1016/j.jvs.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes of vertebral artery injury

Abstract: Neurologic sequelae attributable to VAI were rare. Grade of VAI or vertebral artery segment did not correlate with morbidity. We did not observe any differences in short-term outcomes between systemic anticoagulation and antiplatelet therapy. Of those patients seen at follow-up, injury resolution or stability was documented by CTA. A conservative approach with either observation or antithrombotic therapy is suggested. If the natural history of VAI includes a very low stroke rate, then therapies with a lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
1
21
0
6
Order By: Relevance
“…In this regards, the efficacious results with aspirin have innumerous advocates. [22] These findings support that both the fracture pattern described above and facet dislocations are a strong indicator of potential BVAI. As CT angiography has shown a 99% accuracy compared with conventional angiography in the identification of such injuries, these studies are likely responsible for the recent marked increase in detection of BVAI and should be used in the screening for all patients with this pattern of atlanto-axial injury.…”
Section: Discussionsupporting
confidence: 72%
“…In this regards, the efficacious results with aspirin have innumerous advocates. [22] These findings support that both the fracture pattern described above and facet dislocations are a strong indicator of potential BVAI. As CT angiography has shown a 99% accuracy compared with conventional angiography in the identification of such injuries, these studies are likely responsible for the recent marked increase in detection of BVAI and should be used in the screening for all patients with this pattern of atlanto-axial injury.…”
Section: Discussionsupporting
confidence: 72%
“…As posterior circulation ischemia may occur, consensus recommendations include early screening for cerebrovascular injury following blunt trauma, provided that no contraindication for IV contrast exists and the patient is sufficiently medically stable to undergo imaging 2 19. Prospective studies have repeatedly demonstrated the utility of early initiation of systemic heparin or antiplatelet therapy in reducing the risk of stroke after a blunt cerebrovascular injury 9 21–24.…”
Section: Discussionmentioning
confidence: 99%
“…It lies anterior to the intervertebral foramen between the C-6 and C-7 and then enters the lateral mass of the C-7 transverse process. 1 The C-7 nerve emerges at this level. Preparation of the passage from the intervertebral foramen to the retroesophageal space requires us to traverse deep to the scalenus anterior muscle and through the longus colli muscle.…”
Section: Complications Arising From the Creation Of The Retroesophagementioning
confidence: 93%